Kajian Semiotik Ornamen Interior Pada Lamin Dayak Kenyah ( Studi Kasus Interior Lamin Di Desa Budaya Pampang) - Maria Sicilia Mayasari; Lintu Tulistyantoro; M. Taufan Rizqy (Intra, 2014)
Know of a tribe not only understand how the tribe to survive and adapt , but can not be separated from knowing local customs / values are used . Likewise with the Dayak Kenyah in East Kalimantan that have unique customs and practice . Not only from daily uniqueness , but also of their crafts in the form of carved ornaments . Symbols and ornaments is not only the customary ritual objects but also on the equipment and the traditional long house ( Lamin ) . Just like other tribes in Indonesia , the Dayak Kenyah ornaments also has a meaning and significance in each symbol , so it is interesting to study . Used to assess these semiotic theory proposed by Pierce , which is a study of this method to obtain the meaning of a sign or symbol , function , and relevance of signs to one another . The existence of symbols and ornaments is closely related to the ancestors animism dynamism Dayak Kenyah.